2014
DOI: 10.1371/journal.pone.0101104
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Using Two Populations Reveals Genes and Alleles Controlling Wood Traits and Growth in Eucalyptus nitens

Abstract: Eucalyptus nitens is a perennial forest tree species grown mainly for kraft pulp production in many parts of the world. Kraft pulp yield (KPY) is a key determinant of plantation profitability and increasing the KPY of trees grown in plantations is a major breeding objective. To speed up the breeding process, molecular markers that can predict KPY are desirable. To achieve this goal, we carried out RNA-Seq studies on trees at extremes of KPY in two different trials to identify genes and alleles whose expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
2
15
1
Order By: Relevance
“…In total, 20,984±43 genes, that is about 58 % of E. grandis identified genes, were evenly expressed in the three E. urophylla x E. grandis hybrid genomes. The much higher number of non-DE genes compared to DE genes is consistent with findings of Thavamanikumar et al (2014) in xylem of E. nitens, and may be at least partly attributable to housekeeping genes that are constitutive genes required for the maintenance of basic cellular function and are expressed at relatively constant levels. Nevertheless such a low proportion of DE genes in our experiment was not expected given the natural differential expression existing between the urophylla and grandis parental species (Salazar et al, 2013), the disturbance in the regulation of gene expression often observed in interspecific hybrids (Hegarty et al, 2008) notably concerning the trans-regulatory mechanisms, the possible allele-specific expression mechanism (Song, 2016), and the open field cultivation conditions.…”
Section: Genotypic Effect On Transcript Abundance Between Genotypessupporting
confidence: 81%
“…In total, 20,984±43 genes, that is about 58 % of E. grandis identified genes, were evenly expressed in the three E. urophylla x E. grandis hybrid genomes. The much higher number of non-DE genes compared to DE genes is consistent with findings of Thavamanikumar et al (2014) in xylem of E. nitens, and may be at least partly attributable to housekeeping genes that are constitutive genes required for the maintenance of basic cellular function and are expressed at relatively constant levels. Nevertheless such a low proportion of DE genes in our experiment was not expected given the natural differential expression existing between the urophylla and grandis parental species (Salazar et al, 2013), the disturbance in the regulation of gene expression often observed in interspecific hybrids (Hegarty et al, 2008) notably concerning the trans-regulatory mechanisms, the possible allele-specific expression mechanism (Song, 2016), and the open field cultivation conditions.…”
Section: Genotypic Effect On Transcript Abundance Between Genotypessupporting
confidence: 81%
“…Complementing genetic information with molecular phenotypes (e.g., transcript levels) can contribute to a better mechanistic understanding of trait variation (24,26,27). Expression QTL (eQTL) analysis (28) allows the identification of genomic loci associated with variation in molecular phenotypes.…”
Section: Significancementioning
confidence: 99%
“…RNA-seq technology has been used to investigate the development and 38 E. grandis genes are identified to locate in bona fide lignification clades and 17 genes may be involved in lignin biosynthesis in E. grandis (Carocha et al 2015). In E. nitens, 3953 transcripts have identified to be involved in biotic and abiotic stress response (Thavamanikumar et al 2014). In Eucalyptus grandis and E. urophylla, integrated analysis of transcript and trait variation in eucalypt hybrids could be useful in investigation of wood property traits (Kullan et al 2012).…”
Section: Eucalyptusmentioning
confidence: 99%